Detecting surface inhomogeneity of asteroids - Mnisi, Mandlenkosi (Department of Astronomy, 2025)
This thesis investigates the detection of surface composition inhomogeneity on asteroids using time-series spectroscopy and photometry. Observations were conducted on three test cases—Pluto, asteroid 2005 EK70, and the weather satellite Meteosat-11 using the Mookodi instrument on the Lesedi telescope. For Pluto, time-resolved spectroscopy revealed methane ice absorption bands, with band depths varying between 3.33% and 4.80%, consistent with previously reported values. Photometric analysis supported these results, showing an r − i colour variation linked to surface inhomogeneity. For asteroid 2005 EK70, no significant spectral variations were detected, suggesting a uniform surface composition. The asteroid's diameter was determined to be 1.25 ± 0.26 km, with a rotation period of 4.34 hours, indicating it is stable. The third test case, Meteosat-11, served as a control to verify Mookodi's ability to track stationary objects. These findings demonstrate the capability of ground-based instruments like Lesedi to detect surface composition inhomogeneity from Earth. Future work could further refine these methods and apply them to a wider range of solar system objects.